Pengaruh Media Sosial WhatsApp Terhadap Pengelolaan Konflik Di Sekolah SMA Santo Thomas 2 Medan: Dampak Penggunaan WhatsApp terhadap Strategi Penyelesaian Konflik di SMA Santo Thomas 2 Medan - Sinurat, Lediana; Sitanggang, Nathanael; Simaremare, Aman (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2025)
This study aims to find and analyze the influence of WhatsApp social media on conflict management at SMA Santo Thomas 2 Medan. This study uses a quantitative approach with a descriptive design to describe the relationship between WhatsApp use and conflict dynamics between students. Data were collected through closed questionnaires distributed to 60 grade X students selected using stratified random sampling techniques. The research instrument has been tested for validity and reliability to ensure measurement accuracy. The results of the analysis show that there is a significant influence of WhatsApp use and conflict management, with a contribution of 33% to the variation in conflict management in schools. In conclusion, WhatsApp can play a positive role in helping communication and accelerating conflict resolution if used wisely. These findings are expected to be a reference for schools in managing social media to create a healthy communication environment.